"Can Lightning Strike?" The Importance of Ludonarrative Design in Improving Women’s Representation in Videogames: A Comparative Ludonarratological Analysis of the Hero’s Journey in Final Fantasy 13 and Final Fantasy 15 - Mior Azli, Yang Safia; Philip, Susan; Kaur, Surinderpal (SARE: Southeast Asian Review of English, 2023)
At E3 2006, Square Enix (SE) shocked the game world with its first ever heroine to headline a mainline Final Fantasy game. Its game director, Motomu Toriyama, believed that Final Fantasy 13 (FF13) would provide a unique gaming experience because fans would be able to play as the strong and enigmatic Lightning - a departure from the cute and innocent female characters that are usually found in the franchise. At the time, this was considered a step forward for gender inclusivity in videogames. Despite being a technologically advanced nation where videogames are consumed at all ages, Japan has a long-standing issue when it comes to addressing gender inequality; the problem is challenging due to the country’s strong collectivist mindset that upholds conservative gender ideals. Considering this, we are interested to study how FF13 depicts Lightning as an empowering figure when the context it comes from is rife with sexism. In order to determine whether Lightning’s portrayal as a hero is empowering or problematic, we will be focusing on how her hero’s journey is constructed through the analysis of FF13’s ludonarrative features.